Cancer diagnosis and treatment platform based on manganese-based nanomaterials - Fei, Jia; Liu, Yanyan; Zeng, Ya; Yang, Mingqi; Chen, Shanshan; Duan, Xiaobing; Lu, Ligong; Chen, Muhe (Frontiers in Bioengineering and Biotechnology, 2024)
Cancer is a leading cause of death worldwide, and the development of new diagnostic and treatment methods is crucial. Manganese-based nanomaterials (MnNMs) have emerged as a focal point in the field of cancer diagnosis and treatment due to their multifunctional properties. These nanomaterials have been extensively explored as contrast agents for various imaging technologies such as magnetic resonance imaging (MRI), photoacoustic imaging (PAI), and near-infrared fluorescence imaging (NIR-FL). The use of these nanomaterials has significantly enhanced the contrast for precise tumor detection and localization. Moreover, MnNMs have shown responsiveness to the tumor microenvironment (TME), enabling innovative approaches to cancer treatment. This review provides an overview of the latest developments of MnNMs and their potential applications in tumor diagnosis and therapy. Finally, potential challenges and prospects of MnNMs in clinical applications are discussed. We believe that this review would serve as a valuable resource for guiding further research on the application of manganese nanomaterials in cancer diagnosis and treatment, addressing the current limitations, and proposing future research directions.